Case – Control study: Evaluation of plasma procalcitonin concentration as an indicator of inflammation in healthy and sick cows. (February 2023) - Bonelli, Francesca; Madrigali, Alessio; Sgorbini, Micaela; Meucci, Valentina; Battaglia, Federica; Guélat-Brechbuehl, Monika; Sala, Giulia; Meylan, Mireille
Abstract: This case – control study aims to evaluate Procalcitonin (PCT) plasma concentrations in healthy and hospitalized cows with a conclusive diagnosis of inflammation due to bacterial infection. Thirty-four healthy and 131 sick cows were included. Procalcitonin concentrations were assessed using an ELISA kit for cattle. Depending on whether sick cows received antimicrobial treatments prior to admission or not, they were divided in treated (TP) or not treated (NTP) subgroups. Mann-Whitney U tests were performed to determine differences between healthy vs sick cows, while Kruskal-Wallis with Dunn's multiple comparison test were applied for healthy vs sick subgroups. Receiver operating characteristic (ROC) analysis was performed to assess the optimal cut-off value. Kaplan-Meier survival curves were determined for cows belonging to the groups with PCT values below and above ROC cut-offs. Plasma PCT concentration was 200.1 (147.8–324.1) pg/mL and 361.6 (239.7–947.1) pg/mL in the healthy control and in the sick group, respectively ( P < 0.001). The optimal cut-off value of plasma PCT concentration was 244.4 pg/mL (sensitivity 73.6%, specificity 60.0%). The plasma PCT concentration was 267.5 (210.3–771.2) pg/mL in the TP subgroup and 425.6 (253.1–1242) pg/mL in the NTP subgroup ( P = 0.03). Cows with PCT above the ROC cut-off value had a reduced survival percentage and a higher mortality risk ( P < 0.05). Procalcitonin showed the ability of differentiate healthy cows from hospitalized cows with a conclusive diagnosis of inflammation due to bacterial infection. Moreover, PCT was a good predictor of negative prognostic outcome. Highlights: Plasma procalcitonin represents a parameter for bacterial infection in cows. At admission, procalcitonin was higher in not treated cows compared to the treated. Procalcitonin may have a prognostic value in cows affected by bacterial infection.